2017
DOI: 10.1002/nau.23277
|View full text |Cite
|
Sign up to set email alerts
|

Severe depression and anxiety in women with overactive bladder

Abstract: Moderate or severe depression and anxiety are prevalent in women with OAB. There is a correlation between intensity of OAB symptoms with depression and anxiety. Anxiety and depression levels are mainly related with urgency incontinence and nocturia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 27 publications
3
42
0
1
Order By: Relevance
“…In the Korean study by Lim et al, the US studies by Lai et al, and a similar Brazilian study by Melotti et al, UI severity was positively correlated with anxiety, depression, and stress measures, even when different outcome measures were used. 57, 23, 25 The consistency of these results improve the credibility of our findings that worsening UI severity is an important factor associated with mental health. In women reporting UI in our study, UI severity scores ranged from 1.84–9.44.…”
Section: Discussionsupporting
confidence: 78%
“…In the Korean study by Lim et al, the US studies by Lai et al, and a similar Brazilian study by Melotti et al, UI severity was positively correlated with anxiety, depression, and stress measures, even when different outcome measures were used. 57, 23, 25 The consistency of these results improve the credibility of our findings that worsening UI severity is an important factor associated with mental health. In women reporting UI in our study, UI severity scores ranged from 1.84–9.44.…”
Section: Discussionsupporting
confidence: 78%
“…Some authors, for example, examined the connection between LUTS and suicidal ideation in 2,890 men aged 40 or older using data from the National Health and Nutrition Examination Survey (NHANES) [23]. A recent cross-sectional study with 274 young women showed that moderate to severe depression could be found in 59.8% of OAB patients [12]. History of gynecological surgery is a factor that may lead to depression in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study controlling for age as a confounding variable found that patients with depression have worse OAB symptoms, and their quality of life is more seriously affected compared to those without depression [6]. Similarly, Melotti et al showed a correlation between severe depression and OAB symptoms [12]. In a study with 2,877 women aged 65 years or older, Sexton et al found that depression was an important factor to the worsening of OAB symptoms [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary incontinence has a devastating impact on QoL as it demonstrates loss of bodily control in its most inconvenient and unpleasant way, make LUT care the most challenging issue in the patient's daily life, and can itself drive patients into depression [198][199][200]. Furthermore, urinary incontinence can negatively affect the skin due to frequent contact with urine and/or the necessity to wear pads or diapers which facilitates the development of wounds/ulcerations and dermal infections [201][202][203].…”
Section: Restoration Of Urethral Urine Storage Functionmentioning
confidence: 99%